HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH DI RUANG PERINATOLOGI RSUD H ABDUL MANAP KOTA JAMBI - Ruwayda Ruwayda; M. Dody Izhar (Poltekkes Kemenkes Jambi, 2018)
ABSTRACT Babies with low birth weight (LBW) are babies born with a body weight of less than 2,500 grams. In Jambi Province the incidence of LBW reached 7.12% and the incidence of LBW in the H Abdul Manap General Hospital in Jambi City increased. This study is an analytical survey study with a case control design, to determine the relationship of age and parity with the incidence of LBW using secondary data medical records at H Abdul Manap Hospital in Jambi City. The population was all mothers who gave birth as many as 612 mothers. Case samples were 49 women who gave birth to LBW and 49 women gave birth to normal babies. The sampling technique is total sampling while the control sample uses simple random sampling. The results showed that 19 (38.8%) respondents were at risk and 30 (61.2%) respondents were not at risk. Furthermore, 29 (59.2%) respondents had risky parity and 20 (40.8%) respondents were not risky parity. The statistical test results obtained p-value 0.00 <0.05 means that there is a relationship of age with the incidence of LBW with an OR value (9.71), and parity with a p-value of 0.02 <0.05 means that there is a relationship with the incidence of LBW, OR (2.49). It is expected that the hospital will provide education about the care of pregnancy, especially during the antenatal examination in the class of pregnant women including an explanation of the distribution of iron, vitamins, and folic acid.